Real Time Analysis using Hadoop (International Journal of Engineering and Computer Science, 2018)
: This is an age of BIG DATA. There is huge development in all science and engineering domains which expands big data tremendously. Tweets are considered as raw data and such a huge amount of raw data can be analyzed and represented in some meaningful way according to our requirement and processes. This work provides a way of sentiment analysis using apache hadoop which will process the large amount of data on a hadoop and storm faster in real time. Apache kafka is used here along with apache hadoop and storm as a queuing system. Sentiment analysis of the tweets from the twitter is done to know who the favourite in the tournament is.